The Management Of Inclusion Learning At Elementary School State Blotongan 3 Salatiga - Muhlisun, Muhlisun (2012)
This study has three objectives. The first objective is to describe the characteristic of classroom design at Elementary School State Blotongan 3 Salatiga. The second objective is to elaborate the characteristic of teaching and learning interaction at Elementary School State Blotongan 3 Salatiga. And finally, this study aims to describe the characteristic of learning evaluation at Elementary School State Blotongan 3 Salatiga. It is a qualitative research which was done at Elementary School State Blotongan 3 Salatiga. During the research paper process, it involved several informants such as the principal, teacher and parents. In collecting data, this study used observation, interview, and documentation. Data collection technique used an analysis model of data collection, data reduction, data display, and drawing conclusion. Data validity of this research paper includes credibility, transferability, dependability, and confirmability. This finding suggests that the available facilities and infrastructure are very needed to support teaching and learning activity in school. The existence of inclusion students in the general class does not change the classroom design. Generally, the classroom is designed by arranging the table and chairs to face the blackboard. Inclusion students are placed in the front row for facilitating teacher to help their difficulties. Generally, teaching and learning activities in the inclusion class is the same as the teaching and learning activity in the regular class whether in the strategy, activity, media and the method. The use of varied instructional methods is able to make the students not to get bored in following the teaching and learning activity. The students' interaction is influenced by the content of material delivered by teacher and physical condition of students. The inclusion students begin to be difficult to interact when teaching and learning activity more than two hours. The evaluation can be done every day when teacher finishing a material. Kind of evaluation usually consists of three activities such as written evaluation, spoken, evaluation in the form of tasks. Teachers of Elementary School State Blotongan 3 Salatiga have problems in determining the result of the evaluation. Due to the inclusion students must follow a predetermined standard score. Whereas, the inclusion student' score is under the standard score. Teacher gives the material in a remedial and enrichment.